Pendampingan Penyusunan Pelaporan Keuangan UMKM Kabupaten Bogor - Jasmadeti, Jasmadeti; Tartilla, Nilda; Amrulloh, Amrulloh (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The aim of PKM is to provide knowledge and assistance regarding recording financial reports in accordance with applicable accounting standards. In this case, it is based on the lack of understanding and knowledge possessed by MSMEs in the District. Bogor. The solution we implement in PKM activities related to existing problems is to provide knowledge and skills regarding organized financial recording and compiling financial reports and making financial reports in accordance with applicable accounting standards. In implementing this PKM, the mentoring methods we use are (1) The preparation and socialization stage related to the preparation of training materials and determining easy and enjoyable delivery methods, (2) The implementation stage of assistance in preparing financial reports, namely introducing the concept of recording, preparing and producing related financial reports. financial transactions that occur in UMKM Kab. Bogor aims to provide direct experience related to how to record and journal MSME financial transactions. (3) The third stage of monitoring aims to see the achievement of the targets of the PKM program being carried out. The target to be achieved is to increase understanding in recording, compiling and producing financial reports in accordance with applicable accounting standards. Keywords: Financial Reports, MSMEs